Letter (copy) : Basque Children - Letter from Eastbourne - Middleton, J. S.
038-0061-001 H.V. Tewson. Secretary's. Mr. J.S. Middleton. 13th November, 1939. BASQUE CHILDREN - LETTER FROM EASTBOURNE. I think the line to take with the letter from the Eastbourne Divisional Labour Party is as follows:- Children are in the care of the National Committee for the Care of Basque Children, and upon this Body both the Labour Party and the T.U.C. are represented. The whole position, as is suggested, creates some considerable difficulty, but it is not likely that the children will become a charge on public funds. We quite appreciate the concern of those who have been actively associated with this work and can give assurances that there will be no hasty shelving of our responsibilities to the children who have been brought here. As a matter of fact, practically all the orphans have been privately "adopted", and in many cases the older children are being placed in employment with, of course, full regard to their welfare. The representatives of the Movement on the National Committee are very carefully watching the position and you may rest assured that they will act with a full recognition of the necessity for protecting the children. 292/946/38/61